2010
DOI: 10.1016/j.virol.2010.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus E1 and E2 mediated DNA replication is not arrested by DNA damage signalling

Abstract: Integration of human papillomaviruses into that of the host promotes genomic instability and progression to cancer; factors that promote integration remain to be fully identified. DNA damage agents can promote double strand breaks during DNA replication providing substrates for integration and we investigated the ability of DNA damage to regulate HPV E1 and E2 mediated DNA replication. Results demonstrate that HPV E1 and E2 replication is not arrested following DNA damage, both in vivo and in vitro, while repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 36 publications
5
45
0
Order By: Relevance
“…Our results also suggest that ATR may negatively regulate viral genome replication through NF-B activation. Previously, King et al reported that activation of DDR by etoposide had no effect on E1-dependent replication in a transient replication assay using 293T cells (58). Their results are in agreement with our finding of a minor effect of ATM since etoposide primarily induces DSBs by inhibiting topoisomerase II (59).…”
Section: Activation Of Nf-b By E1 Through Ddrsupporting
confidence: 93%
“…Our results also suggest that ATR may negatively regulate viral genome replication through NF-B activation. Previously, King et al reported that activation of DDR by etoposide had no effect on E1-dependent replication in a transient replication assay using 293T cells (58). Their results are in agreement with our finding of a minor effect of ATM since etoposide primarily induces DSBs by inhibiting topoisomerase II (59).…”
Section: Activation Of Nf-b By E1 Through Ddrsupporting
confidence: 93%
“…In the context of HPV, it is tempting to speculate that the presence of p80 at the replication fork may facilitate the recruitment of DDR proteins to promote viral DNA replication or, conversely, to alleviate problems linked with a stalled replication fork. However, we and others recently showed that DNA damage neither interferes with nor stimulates transient HPV DNA replication (18,31), suggesting that the effect of p80 in this context is independent of DDR signaling. Furthermore, Moody et al also observed, using the chemical inhibitor KU-55933, that the ATM pathway has no effect on the stable maintenance of the HPV episome in undifferentiated keratinocytes (40), in contrast to p80, whose interaction with E1 is essential for this process (12).…”
mentioning
confidence: 73%
“…In fact, it has been shown that papillomaviruses amplify their DNA in the G 2 phase of the cell cycle in cells that have already completed S phase (6) and that efficient amplification of the viral genome requires an activated ATM response in differentiated cells (39). The DNA damage response does not seem to interfere with HPV DNA replication, since a recent study showed that transient viral replication is not inhibited by DNA damage-inducing agents, indicating that E1 and E2 can replicate the viral genome in the presence of a DNA damage response (28).…”
Section: Discussionmentioning
confidence: 99%